CULTURAL APPROACH TO TEACH ENGLISH: MUSIC AS A TEACHING AND THERAPY IN LEARNING ENGLISH - Dianti Putri, Nurma; Mohd Ridwan, Natashah; Sri Lestari, Dinda; Husniah, Nabilatul; Taufik Ihsan, Muhammad (CV RIFAINSTITUT, 2021)
This research aims about how effective music as a teaching and therapy in learning English. Music makes ELT class more enjoyable and powerful for students. The explanation in this research is about what is the factors affecting pronunciation, what is the advantages of using song in ELT class and how can English songs facilitate English language learning. This research is using qualitative data collection for 50 students in Senior High School of St. Mary, Surabaya. The observation were made from the questionnaire, interviews and participants observation. One possible academic application is to encourage the students to listen to English music and input it in ELT class. Music, a mix of melody and lyrics, has numerous characteristic benefits, like a kaleidoscope of culture, expressiveness, creditability and helpful capacities, which render it a priceless hotspot for language educating. Learning through music is one of the best and easier for students to understand English. The way that English music for the students are frequently simple and straightforward point that they like most to learn. This research gives effective factors, benefits and facilitate in inserting music as a teaching and learning during ELT class.